2009
DOI: 10.1007/s10393-009-0238-9
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Habitat Size, Brushtail Possum Density, and the Mosquito Fauna of Native Forests in the Auckland Region, New Zealand

Abstract: Human activities have been causing dramatic and unprecedented changes to the Earth's ecosystems, and are a primary factor associated with biological invasions. Disturbed and fragmented habitats allow some vector mosquitoes to thrive. The New Zealand landscape has been extensively modified since the arrival of humans, and there is accumulating evidence that the distribution of mosquitoes is being altered as a result of anthropogenic environmental changes. This study aimed to assess whether forest habitat size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…The ecological findings of this study also support data from previous work on mosquitoes in the Auckland region, as A. antipodeus was also the most abundant native species recorded in other tracts of native forest (Derraik et al 2005b;Derraik 2009a). This species breeds in temporary ground pools in areas with partial or dense shade (Belkin 1968), and our results and previous findings (Derraik et al 2005a;Derraik 2009a) suggest that relatively pristine mature forests provide greater availability of suitable larval habitats.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The ecological findings of this study also support data from previous work on mosquitoes in the Auckland region, as A. antipodeus was also the most abundant native species recorded in other tracts of native forest (Derraik et al 2005b;Derraik 2009a). This species breeds in temporary ground pools in areas with partial or dense shade (Belkin 1968), and our results and previous findings (Derraik et al 2005a;Derraik 2009a) suggest that relatively pristine mature forests provide greater availability of suitable larval habitats.…”
Section: Discussionsupporting
confidence: 90%
“…Our results corroborate previous findings showing that forest fragmentation in the Auckland region favours introduced mosquito species, which were nearly absent from large tracts of native forest (Derraik et al 2005a;Derraik 2009a). Given both C. quinquefasciatus and A. notoscriptus are vectors of human and animal disease (Derraik 2004), this study adds further evidence that anthropogenic environmental change is associated with an increased transmission risk of vector-borne diseases, particularly in the more densely populated Auckland region.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…20 Furthermore, the species appears to be favored by anthropogenic environmental change and it is therefore likely to continue to spread into previously unoccupied habitats such as human-modified native forests. 24 Aedes notoscriptus mosquitoes are not only highly anthropophilic but also a vector of Alphavirus in Australia, where they are believed to be important vectors of Ross River virus (RRV) in urban areas. 25 A recent laboratory study found Ae.…”
Section: New Zealandmentioning
confidence: 99%